2013
DOI: 10.1097/mcg.0b013e318299c69d
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitor-induced Gastrointestinal Angioedema

Abstract: This series highlights ascites as a key feature that distinguishes ACE inhibitor-induced gastrointestinal angioedema from infectious enteritis. This series also confirms the increased incidence of this condition among African American women, an unpredictable interval between medication initiation and the development of symptoms, and the heightened probability of symptom recurrence if ACE inhibitors are not discontinued. ACE inhibitor-induced gastrointestinal angioedema is a rare cause of acute abdominal compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…A lump in the throat, drooling, stridor and a hoarse voice or aphonia are possible symptoms, when the airways are involved, signalling a severe situation with the need to act immediately and secure the airway (16,22). Abdominal pain might be a rare and sometimes the only sign of ACEi-induced angioedema, since the swellings can be present solely in the abdominal organs, most often the intestines (29,30).…”
Section: Clinical Presentationmentioning
confidence: 98%
“…A lump in the throat, drooling, stridor and a hoarse voice or aphonia are possible symptoms, when the airways are involved, signalling a severe situation with the need to act immediately and secure the airway (16,22). Abdominal pain might be a rare and sometimes the only sign of ACEi-induced angioedema, since the swellings can be present solely in the abdominal organs, most often the intestines (29,30).…”
Section: Clinical Presentationmentioning
confidence: 98%
“…Symptoms of ACEi-induced angioedema are usually localized in the face or upper aerodigestive tract; the main characteristic is erythema (without itching) lasting 24–72 h, followed by spontaneous remission [27]. Reports of rare abdominal involvement have been published [28]. ACEi-induced angioedema has been reported as a side effect affecting 0.1–0.7% of patients and up to 1.6% in some studies [29]; a large US study reported an incidence of 0.2% [30].…”
Section: Reviewmentioning
confidence: 99%
“…Using search terms “intestinal angioedema,” “visceral angioedema,” “ACE‐inhibitor side effects,” and the names of ACE inhibitors such as lisinopril, captopril, enalapril, benazepril, a list of articles were compiled from 1980 to 1 August 2016. Thirty‐four individual reports of ACE inhibitor induced visceral angioedema fit the criteria in question . Signature features to assist in diagnosing ACEi‐induced intestinal type angioedema are denoted in Table and are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…From the information gathered, there are several trends throughout the case reports. There is a disproportionate number of women affected (85%) compared to men . The age of patients ranged from 26 to 92 years, with the average age being 49.5 years (SD = 15.3) Ethnicity was only reported in 15 cases, nine of which reported the patient being African American .…”
Section: Discussionmentioning
confidence: 99%